The Effect of Cognitive-Motor Dual Tasks on the Risk of Falls in Female Saudi Students: A Cross-Sectional Study - Alatawi SF; Mahmoud HM (Risk Management and Healthcare Policy)
Salem F Alatawi,1 Hayam M Mahmoud2 1Department of Health Rehabilitation Sciences, Faculty of Applied Medical Sciences, University of Tabuk, Tabuk, Saudi Arabia; 2Department of Medical Rehabilitation Science, Faculty of Applied Medical Sciences, Umm Al-Qura University-Makkah-Saudi Arabia; Cairo University, Cairo, EgyptCorrespondence: Salem F Alatawi, Department of Health Rehabilitation Sciences, Faculty of Applied Medical Sciences, University of Tabuk, Tabuk City, Saudi Arabia, Tel +966144563434, Email sfalatawi@ut.edu.saIntroduction: Dual tasking (DT) requires individuals to carry out two actions simultaneously, comparable to how the brain can perform a cognitive function while the body is in motion, which eventually enhances human balance. This paper aims to examine and compare the impact of DT on the risk of falling (ROF) among Saudi female students.Methods: A cross-sectional design was used. 120 female students were recruited and divided into two groups: literary group (LG) (n = 34) and scientific group (SG) (n = 86). Participants, aged 18– 25, had a normal body mass index (BMI) and cognitive and balancing skills. ROF was measured using the Biodex balancing device for balance alone (no DT) and with DT (motor and two cognitive tasks). After three trials, the mean and average were calculated. The ICC calculation showed a reliable result of < 0.8. BMI was represented as the mean (M) and standard deviation (SD) for both groups. ROF was compared within and between groups using paired and unpaired T-tests. Mann–Whitney compared the two groups throughout DT. The level of significance was P = 0.05.Results: There was no significant difference in ROF in SG (P = 0.06) between the performance with and without a DT; on the contrary, LG demonstrated a significant difference (P = 0.001) for the same tests. In addition, the only time there was a significant difference between the two groups was when they performed DT (P = 0.006).Conclusion: Female students who used critical and analytical thinking and motor performance in their study and daily routine were more balanced and resistant to falling than their peers who did not. This study may improve efficient treatments for fall prevention and balance. Future research could investigate the complex nature of additional DT that may be complicated by gender and BMI outside of the normal range.Keywords: dual tasks, risk of fall, cognition, balance